Cultural sovereignty beyond the modern state : space, objects, and media - Mende, Silke; Ṿais, Yifʿat; Ashipala, Saima Nakuti; Lambertz, Sebastian; Brendebach, Jonas; Volkmer, Ingrid; Cremer, Fabian (2021)
In the past 25 years or more, political observers have diagnosed a crisis of the sovereign nation state and the erosion of state sovereignty through supranational institutions and the global mobility of capital, goods, information and labour. This edition of the European History Yearbook seeks to use "cultural sovereignty" as a heuristic concept to provide new views on these developments since the beginning of the 20th century.